Venom proteome of Bungarus sindanus (Sind krait) from Pakistan and in vivo cross-neutralization of toxicity using an Indian polyvalent antivenom - Oh, Angeline Mei Feng; Tan, Choo Hock; Tan, Kae Yi; Quraishi, Naeem H.; Tan, Nget Hong (Elsevier, 2019)
The proteome of the Pakistani B. sindanus venom was investigated with reverse-phase HPLC and nano-ESI-LCMS/MS analysis. At least 36 distinct proteins belonging to 8 toxin protein families were identified. Three-finger toxin (3FTx), phospholipase A2 (including β-bungarotoxin A-chains) and Kunitz-type serine protease inhibitor (KSPI) were the most abundant, constituting ~95% of total venom proteins. The other toxin proteins of low abundance are snake venom metalloproteinase (SVMP), L-amino acid oxidase (LAAO), acetylcholinesterase (AChE), vespryn and cysteine-rich secretory protein (CRiSP). The venom was highly lethal to mice with LD50 values of 0.04 μg/g (intravenous) and 0.15 μg/g (subcutaneous). The 3FTx proteins are diverse, comprising kappa-neurotoxins, neurotoxin-like protein, non-conventional toxins and muscarinic toxin-like proteins. Kappa-neurotoxins and β-bungarotoxins represent the major toxins that mediate neurotoxicity in B. sindanus envenoming. Alpha-bungarotoxin, commonly present in the Southeast Asian krait venoms, was undetected. The Indian VINS Polyvalent Antivenom (VPAV) was immunoreactive toward the venom, and it moderately cross-neutralized the venom lethality (potency = 0.25 mg/ml). VPAV was able to reverse the neurotoxicity and prevent death in experimentally envenomed mice, but the recovery time was long. The unique toxin composition of B. sindanus venom may be considered in the formulation of a more effective pan-regional, polyspecific antivenom. Biological significance: Bungarus sindanus, an endemic krait species distributed mainly in the Sindh Province of Pakistan is a cause of snake envenomation. Its specific antivenom is, however, lacking. The proteomic study of its venom revealed a substantial presence of κ-bungarotoxins and β-bungarotoxins. The toxin profile corroborates the potent neurotoxicity and lethality of the venom tested in vivo. The heterologous Indian VINS polyvalent antivenom (VPAV) cross-reacted with B. sindanus venom and cross-neutralized the venom neurotoxicity and lethality in mice, albeit the efficacy was moderate. The findings imply that B. sindanus and the phylogenetically related B. caeruleus of India share certain venom epitopes. Research should be advanced to improve the efficacy spectrum of a pan-regional polyspecific antivenom.